1987
DOI: 10.1111/j.1570-7458.1987.tb02217.x
|View full text |Cite
|
Sign up to set email alerts
|

Condition and fate of larvae from insecticide‐treated female tsetse flies Glossina palpalis

Abstract: Many larvae from wild‐caught female Glossina palpalis palpalis R.‐D. treated topically with dieldrin or sumicidin or sumithrin or permethrin failed to pupariate and many larvae from mothers treated with sumicidin or sumithrin or neopynamin formed small or malformed puparia which failed to eclode. Puparia produced soon after maternal handling often did not emerge and many produced by flies starved more than 3 days also did not emerge. Very many puparia from dieldrin‐treated mothers failed to emerge and nonemerg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

1987
1987
1993
1993

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…Kwan et al (1982) suggested that the development of tolerance of endosulfan by pregnant G. m. morsitans females was due to partitioning of absorbed insecticide into lipid components of the fat-body or of uterine milk, diverting it from site(s) of lethal action in the maternal fly. The same mechanism is suggested elsewhere by Riordan (1987), who showed that the viability of puparia produced by insecticide-treated females was lowest among those in which larviposition took place three days after maternal treatment, due to preferential partitioning of insecticide into the food of the in-utero larva during its period of maximal feeding (Denlinger & Ma, 1974;Langley & Pimley, 1975). The failure in the present work and other reports (Burnett, 1962a;Hadaway, 1972) to show any markedly increased tolerance of pregnant flies to organophosphates suggests that these insecticides do not undergo any preferential diversion into in-utero larvae, possibly due to the fact that many organophosphates, especially thiophosphates, undergo a metabolic transformation into a lethal form subsequent to absorption, perhaps involving an ionized stage of low lipid solubility.…”
Section: Discussionsupporting
confidence: 75%
See 4 more Smart Citations
“…Kwan et al (1982) suggested that the development of tolerance of endosulfan by pregnant G. m. morsitans females was due to partitioning of absorbed insecticide into lipid components of the fat-body or of uterine milk, diverting it from site(s) of lethal action in the maternal fly. The same mechanism is suggested elsewhere by Riordan (1987), who showed that the viability of puparia produced by insecticide-treated females was lowest among those in which larviposition took place three days after maternal treatment, due to preferential partitioning of insecticide into the food of the in-utero larva during its period of maximal feeding (Denlinger & Ma, 1974;Langley & Pimley, 1975). The failure in the present work and other reports (Burnett, 1962a;Hadaway, 1972) to show any markedly increased tolerance of pregnant flies to organophosphates suggests that these insecticides do not undergo any preferential diversion into in-utero larvae, possibly due to the fact that many organophosphates, especially thiophosphates, undergo a metabolic transformation into a lethal form subsequent to absorption, perhaps involving an ionized stage of low lipid solubility.…”
Section: Discussionsupporting
confidence: 75%
“…Langley & Pimley (1975) concluded, for well-fed G. m. morsitans females, that larvae have received enough nutrients by day 5 to complete in-utero development. It is reported elsewhere (Riordan, 1987) that many full-sized larvae were deposited more than three days after the start of the enforced maternal starvation and could pupariate and ultimately emerge as adults successfully. These findings indicate that the last 3-4 days of in-utero life constitute late pregnancy and that, in the present work, the proportions of larvipositing females among control (acetone-treated) flies and among flies that were treated with the lowest doses of insecticides indicated the true proportion (about 25%) of the test flies that were in late pregnancy.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations